(3EOGQI GdeTQhYGJ GdUZjQIs - (3eGLOI(B, (3GdYWjIs ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2004)
(3eONd Edi GdeTQhYGJ GdUZjQI(B-(3CTcGd GdedcjI ddeTQhYGJ GdUZjQI(B-(3JCSjS GdeTQhY GdUZjQ(B-(3eUGOQ Jehjd GdeTQhYGJ GdUZjQI(B-(3GNJjGQ GdehbY ddeTQhYGJ GdUZjQI(B-(3GOGQI GdeTJQjGJ hGdeSJhOYGJ aj GdeTQhYGJ GdUZjQI(B-(3GdNWI GdJShjbjI aj GdeTQhYGJ GdUZjQI(B-(3bQhV GdYedGA(B-(3GdJCejf hGdeNGWQI hGdSQbI(B-(3GdeMGSHI GdeGdjI ddeTQhYGJ GdUZjQI(B-(3GdHjFI GdCNdGbjI hGdbGfhfjI ddeTGQjY GdUZjQIs
Keywords: (3GdJCejf (B- (3GdHfhcs; (3GdJShjbs; (3GdeMGSHI GdeGdjIs; (3GdeTGQjY GdUZjQIs; (3bQhV GdYedGAs